2022
DOI: 10.1111/jfpp.16697
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sweet potato leaf powder on sensory, texture, nutrition, and digestive characteristics of steamed bread

Abstract: This study investigated the influence of sweet potato leaf powder (SPLP) (0%–16%) on steamed bread quality. Results showed with the addition of SPLP, height/diameter ratio increased from 0.44 to 0.96, specific volume decreased from 2.44 to 1.47, color changed from white to dark green, and hardness, gumminess, and chewiness ascended gradually; the contents of protein, fat, dietary fiber, minerals, vitamin B2, and niacin increased significantly, in particular, the polyphenol content increased from 1.34 to 9.34 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
(47 reference statements)
1
5
0
Order By: Relevance
“…The above results were consistent with the study by Hu et al (2022b), who found that dietary fibre, polyphenols and protein contents in steamed bread were significantly increased after different proportions of sweet potato leaf powder were added, while the specific volume decreased and the height-to-diameter ratio increased. Similarly, Wang et al (2021) and Crockett et al (2011) found that the specific volume of steamed bread and gluten-free bread decreased with the increased addition of insoluble dietary fibre, ferulic acid and soybean protein isolate.…”
Section: Effects Of Dietary Fibres Polyphenols and Proteins On Specif...supporting
confidence: 92%
See 2 more Smart Citations
“…The above results were consistent with the study by Hu et al (2022b), who found that dietary fibre, polyphenols and protein contents in steamed bread were significantly increased after different proportions of sweet potato leaf powder were added, while the specific volume decreased and the height-to-diameter ratio increased. Similarly, Wang et al (2021) and Crockett et al (2011) found that the specific volume of steamed bread and gluten-free bread decreased with the increased addition of insoluble dietary fibre, ferulic acid and soybean protein isolate.…”
Section: Effects Of Dietary Fibres Polyphenols and Proteins On Specif...supporting
confidence: 92%
“…The above results were consistent with the study by Hu et al . (2022b), who found that dietary fibre, polyphenols and protein contents in steamed bread were significantly increased after different proportions of sweet potato leaf powder were added, while the specific volume decreased and the height‐to‐diameter ratio increased. Similarly, Wang et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under the same preparation and baking conditions, the change in color is closely related to the overall contents of the product, especially from elements, pigmented phytochemicals, and precursors of the Maillard reaction [ 94 ]. Furthermore, the increase in fiber and polyphenols could affect the elasticity of dough, thus the texture, roundness, and chewability of the final product [ 84 , 95 ]. These factors combined might contribute to the overall evaluation of the bread.…”
Section: Resultsmentioning
confidence: 99%
“…After the optimal process parameters were determined, the proximate composition of fresh PSP and PSPP was analyzed; among which, the moisture was determined according to GB5009.3–2016, starch was evaluated as described by GB5009.9–2023, total dietary fiber was determined according to GB5009.88–2023, ash was determined according to GB5009.4–2016, fat was determined as described by GB5009.6–2016, and protein was determined via Kjeldahl method and calculated with a nitrogen conversion factor of 6.25 …”
Section: Methodsmentioning
confidence: 99%